Collaborating with Marine Birds to Monitor the Physical Environment Within Coastal Marine Protected Areas - Rachael Orben; Adam Peck-Richardson; Alexa Piggott; James Lerczak; Greg Wilson; Jessica Garwood; Xiaohui Liu; Sabir Muzaffar; Alexa Foster; Humood Naser; Mohamed AlMusallami; Tycho Anker-Nilssen; et al. (Oceanography, 2025)
Animal telemetry is maturing into a viable method for observing the ocean as it can be used to monitor both environmental conditions and biological metrics along the movement trajectories of marine animals. As part of the Cormorant Oceanography Project, we have augmented a biologging tag with an external fast response temperature sensor to collect ocean temperature profiles from the backs of foraging marine birds. Cormorants dive between 50 and 250+ times a day to forage for prey so they can provide hard-to-match temporal and spatial coverage of coastal ocean conditions within their foraging areas. We process tag measurements to obtain fundamental oceanographic data (e.g., temperature profiles, bottom soundings, surface current measurements). Together, we have tracked 17 marine bird species (including two Spheniscus penguins spp. and a sea duck), originating from 17 countries and foraging along the edges of all major oceans. Tagged birds’ distribution included 191 MPAs in 26 countries, offering a unique ocean monitoring method to complement more widely used methods.